Integrasi Higher Order Thinking Skills Dalam Pembelajaran Bahasa Arab - Muzaffar, Asyraf (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2025)
The skills of Indonesian students in higher-order thinking, or Higher Order Thinking Skills (HOTS), in various dimensions are still far from what is expected. It is suspected that the main factor behind this low skill level is that these HOTS dimensions are still not clearly defined. This issue becomes even more unsolvable because teachers, as planners, implementers of teaching and learning activities in the classroom, and the front-line assessors of learning outcomes, have not yet enhanced their knowledge and abilities in HOTS concepts and their implementation. In teaching foreign language subjects, such as Arabic, the integration of HOTS is considered even more challenging due to the nature of the subject, which focuses more on vocabulary learning, language rules, and language skills, often relying solely on lower-order thinking skills. For the Arabic language subject to contribute to building HOTS in students, a reorientation of learning that integrates both language learning objectives and HOTS learning objectives is needed. This formulation of the reorientation of Arabic language learning is carried out by reviewing the theories and frameworks of cognitive processes and knowledge content, and then trying to formulate the orientation of Arabic language learning and adopting other foreign language learning practices. One aspect of this reorientation is to integrate learning activities with teaching materials and instructional procedures that facilitate students in learning, practicing, and absorbing the dimensions of HOTS. With this reorientation, it is hoped that the Higher Order Thinking Skills learning component will become an integral part of Arabic language learning in the classroom.